Imbalance of interleukin‐17‐producing CD4 T cells/regulatory T cells axis occurs in remission stage of patients with hepatitis B virus‐related acute‐on‐chronic liver failure. Issue 3 (26th February 2013) - Zhang, Geng‐Lin; Xie, Dong‐Ying; Lin, Bing‐Liang; Xie, Chan; Ye, Yi‐Nong; Peng, Liang; Zhang, Shao‐Quan; Zhang, Yu‐Feng; Lai, Qing; Zhu, Jian‐Yun; Zhang, Ying; Huang, Yang‐Su; et al.
Abstract Background and Aim Although regulatory T cells (Treg) and interleukin‐17‐producing CD4 T cells (Th17) have been demonstrated to play opposing roles in inflammation‐associated diseases, their frequency and balance in different stages of hepatitis B virus (HBV)‐related acute‐on‐chronic liver failure (ACLF) remain unknown. Methods Fourteen patients with HBV‐associated ACLF were studied and defined into different stages according to disease activity. Circulating Th17 cells and Treg cells were analyzed by flow cytometry, and the cytokines were quantitated by enzyme‐linked immunosorbent assay. Results were correlated with temporal changes in viral load, disease progression and compared with 30 chronic hepatitis B (CHB) subjects and 18 healthy subjects. Results We showed a significantly higher frequency of circulating Th17 cells in the remission stage of ACLF when compared with the progression stage, the CHB group, or normal controls. However, the frequency of circulating Treg cells was significantly lower in the remission stage of ACLF when compared with the progression stage or the CHB group. The increase in Th17 cells and concomitant decrease in Treg cells created an imbalance in the remission stage of ACLF patients, which negatively correlated with disease progression. In addition, we showed that ACLF patients in the remission stage had an altered profile of cytokines that regulated the induction of Th17 cells and Treg cells. Conclusions ACLF patients in the remission stage had an imbalance of Th17 to Treg cells, which could be used as a prognostic marker to predict disease progression. This imbalance could play a role in the immunopathogenesis of HBV‐related ACLF.